2019
DOI: 10.1155/2019/7632852
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Events in Lasers with Modulation of the Field Polarization

Abstract: We develop a theoretical model for a unidirectional ring laser consisting of an isotropic active medium inside a cavity containing a birefringent Kerr cell. We analyze the dynamical behavior of the system as we modulate the voltage applied to the Kerr cell. We discuss the bifurcation diagram and we study the regions of control parameter space where it becomes possible to observe and predict extreme events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Even though the study of EEs and their emerging mechanism in the systems with external forcing are studied and acknowledged by the scientific community, very few studies have been reported the emergence of EEs in parametrically excited nonlinear dynamical systems, especially in laser models 16,[47][48][49] . However, the influence of parametric excitation to induce EEs in other classes of dynamical systems, in particular, macro and micromechanical oscillator models also require immediate attention.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the study of EEs and their emerging mechanism in the systems with external forcing are studied and acknowledged by the scientific community, very few studies have been reported the emergence of EEs in parametrically excited nonlinear dynamical systems, especially in laser models 16,[47][48][49] . However, the influence of parametric excitation to induce EEs in other classes of dynamical systems, in particular, macro and micromechanical oscillator models also require immediate attention.…”
Section: Introductionmentioning
confidence: 99%